Erratum: Li, C.P.; Duan, L.C.; Tan, S.C., et al. Damage Model and Numerical Experiment of High-Voltage Electro Pulse Boring in Granite. Energies 2019, 12, 727 - Changping Li; Longchen Duan; Songcheng Tan; Victor Chikhotkin; Wenpeng Fu (Energies, 2019)
The authors wish to make the following corrections to this paper [...]